Hypoxia-sensitive miRNA regulation via CRISPR/dCas9 loaded in hybrid exosomes: A novel strategy to improve embryo implantation and prevent placental insufficiency during pregnancy - Yaghoobi, Alireza; Nazerian, Yasaman; Meymand, Arman Zeinaddini; Ansari, Ali; Nazerian, Amirhossein; Niknejad, Hassan (Frontiers in Cell and Developmental Biology, 2023)
Assisted reproductive techniques as a new regenerative medicine approach have significantly contributed to solving infertility problems that affect approximately 15% of couples worldwide. However, the success rate of each in-vitro fertilization (IVF) cycle remains only about 20-30%, and 75% of these losses are due to implantation failure (the crucial rate-limiting step of gestation). Implantation failure and abnormal placenta formation are mainly caused by defective adhesion, invasion, and angiogenesis. Placental insufficiency endangers both the mother's and the fetus's health. Therefore, we suggested a novel treatment strategy to improve endometrial receptivity and implantation success rate. In this strategy, regulating mir-30d expression as an upstream transcriptomic modifier of the embryo implantation results in modified expression of the involved genes in embryonic adhesion, invasion, and angiogenesis and consequently impedes implantation failure. For this purpose, "scaffold/matrix attachment regions (S/MARs)" are employed as non-viral episomal vectors, transfecting into trophoblasts by exosome-liposome hybrid carriers. These vectors comprise CRISPR/dCas9 with a guide RNA to exclusively induce miR-30d gene expression in hypoxic stress conditions. In order to avoid concerns about the fetus's genetic manipulation, our vector would be transfected specifically into the trophoblast layer of the blastocyst via binding to trophoblast Erb-B4 receptors without entering the inner cell mass. Additionally, S/MAR episomal vectors do not integrate with the original cell DNA. As an on/off regulatory switch, a hypoxia-sensitive promoter (HRE) is localized upstream of dCas9. The miR-30d expression increases before and during the implantation and placental insufficiency conditions and is extinguished after hypoxia elimination. This hypothesis emphasizes that improving the adhesion, invasion, and angiogenesis in the uterine microenvironment during pregnancy will result in increased implantation success and reduced placental insufficiency, as a new insight in translational medicine.